Faktor Demografi WUS yang Berhubungan dengan Status Gizi Berdasarkan LiLA di Puskesmas Pacarkeling Tahun 2017 - Okta Aventi Chusniatul Ainia; Hari Basuki Notobroto (Universitas Airlangga, 2018)
Nutritional status could be determined based on Body Mass Index, Waist circumference, and Mid-Upper Arm Circumference. Weight measurement to check nutritional status, it was known that there were 82.81% of obese sufferers from 70,023 people who were examined. Nutritional status was a condition caused by a balance between food intake and nutritional needs. Good nutritional status was needed if you want to achieve optimal health status.Nutritional status was very important for women of childbearing age in preparation for pregnancy, during pregnancy, childbirth and after childbirth. The purpose of this study was to determine the factors related to nutritional status of women of childbearing age of family planning participants at Pacarkeling Health Center Surabaya in 2017.This study was non-reactive because it used secondary data as a source of analysis. The time of this study was March to April 2018. The age factor showed a p-value of 0.013, which meant significant. The number of live children factor showed a p-value of 0.022, which meant significant. The types od contraception factor showed a p-value of 0.259, which meant not significant. Factors that affect the nutritional status of women of childbearing age of family planning participants at Pacarkeling Community Health Center in 2017 were age and number of live children. For women of childbearing age, it is hoped that it can improve its nutritional status in preparing for pregnancy, pregnancy, childbirth, and postpartum so that there will be no problems in nutritional status in the future. For Pacar Keling Health Center, it can improve the quality of health workers so they can continue to strive for counseling about nutritional status to the community, especially women of childbearing age.